If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(8 + k) = -24 (8 * -6 + k * -6) = -24 (-48 + -6k) = -24 Solving -48 + -6k = -24 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + -6k = -24 + 48 Combine like terms: -48 + 48 = 0 0 + -6k = -24 + 48 -6k = -24 + 48 Combine like terms: -24 + 48 = 24 -6k = 24 Divide each side by '-6'. k = -4 Simplifying k = -4
| -2r6-2r/5 | | -7x+3x=8-6+3+3 | | 7*2-4+9+8*4=36 | | 3p^2+13p-10=0 | | 4n=4+6n | | -2w-3w=12+5 | | 5u-5-5u=u+8 | | 20m^2+54m-25=0 | | 7*2-4+9+8*4= | | 1/x-3=-8 | | 2y+2x=44 | | 2y-3=9y+39 | | 1/x-3=-8/5 | | -2(-6n-4)+2n=-37-n | | 6=6u | | 170=8n-40 | | 1/x-3=20 | | 5-7-2n=95 | | 7(-7+a)=-70 | | 1/x-3=4 | | -68/4=x | | (4x+5)=45 | | 15/3*5-4^2=25 | | 5=-12-3 | | x^2-9+4(x+3)=0 | | 6d=3 | | -(8+d)= | | 5-(7-n)=95 | | -5/4x=4 | | xy+5=x-7 | | 25+5x=3 | | 11x-7=20x-14 |